2011
DOI: 10.1007/s00482-011-1081-9
|View full text |Cite
|
Sign up to set email alerts
|

Pädiatrische Schmerztherapie

Abstract: Pediatric nurses must be trained more efficiently in pediatric pain management so that an adequate pain management is available for children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
2
6
2
1
Order By: Relevance
“…The nurses in the present study had a mean PNKAS-N score of 72%, which is 13% lower than the level of knowledge accepted by most nursing standards (Omari, 2016;Stanley & Pollard, 2013). This level of knowledge is comparable to results found in some studies (Hovde et al, 2012;Johnston et al, 2007;Manworren, 2000;von Lutzau et al, 2011), but lower than in others (Le May et al, 2009;Smart, 2005;Vincent, 2005) that reported total mean PNKAS scores of 77%-81%. Importantly, when examining the range of scores, nurses in the present study scored from 35% to 100%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The nurses in the present study had a mean PNKAS-N score of 72%, which is 13% lower than the level of knowledge accepted by most nursing standards (Omari, 2016;Stanley & Pollard, 2013). This level of knowledge is comparable to results found in some studies (Hovde et al, 2012;Johnston et al, 2007;Manworren, 2000;von Lutzau et al, 2011), but lower than in others (Le May et al, 2009;Smart, 2005;Vincent, 2005) that reported total mean PNKAS scores of 77%-81%. Importantly, when examining the range of scores, nurses in the present study scored from 35% to 100%.…”
Section: Discussionsupporting
confidence: 89%
“…Nurse undertreatment of pain in children and adolescents is a consequence of pain management knowledge deficits, at least in part (Twycross, Forgeron, et al, 2015). The knowledge and attitudes of nurses regarding pediatric pain management has been identified in several studies using the Pediatric Nurses' Knowledge and Attitude Survey Regarding Pain Questionnaire (PNKAS) (Ekim & Ocakcı, 2013;Hovde, Granheim, Christophersen, & Dihle, 2012;Lobete Prieto, Rey Galán, & Kiza, 2015;Lunsford, 2015;Omari, 2016;Ortiz et al, 2015;Stanley & Pollard, 2013;von Lutzau, Hechler, Herzog, Menke, & Zernikow, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stanley & Pollard, 2013;Alatoibi et al, 2018). The psychometric characteristics of the original test version (Manworren, 2001) with a test-retest reliability of 0.67 and Cronbach's alpha ranging between 0.72 and 0.77 were confirmed for the German version (Von Lützau et al, 2010). Eight questions regarding pharmacotherapy with opioids were removed, because opioid agents are not a common medication in child and adolescent psychiatric clinics and answers to theses questions would be at the level of chance.…”
Section: Methodsmentioning
confidence: 93%
“…The questionnaire asked for demographic characteristics such as gender, age, profession, and work experience. To assess the staff's knowledge and attitudes regarding pain, the German version of the PNKAS-Shriner's revision 2002 questionnaire was used (Von Lützau et al, 2010). The permission to use the German version was obtained by the copyright holders at the German Children's Pain Centre in Datteln.…”
Section: Methodsmentioning
confidence: 99%